Proposta de um instrumento de diagnóstico e aplicação em cooperativas da agricultura familiar assessoradas pela Emater/RS - Servat, Marcos Eduardo (2016)
The diagnosis in the organizational environment is considered one of the initial stages of planning and the results are essential to guide the structuring of the following steps within the process. Developed a study that aimed to propose and apply a diagnostic tool for the cooperatives of family farming advised by EMATER / RS. Within this understanding cooperatives play a key role in economic and social conditions of the communities in which they operate. And so they are confronted with the need to improve their management practices. In order to achieve better performance indicators in its local management. In this scenario it was observed that there are few materials that approach the characteristics and peculiarities of the cooperative when it comes to supporting management tools. This study aimed to improve the process of diagnosis, by proposing an instrument for making the diagnosis, considers strategic and characteristic of these cooperatives. The methodology defined the action research. Because the researcher provide all research policies along with the research institution. In other words, a study based on the facts and in need of cooperatives involved in activities related to diagnostic tools. The developed instrument was applied in three cooperatives for the purpose of the study analysis. Thus it was developed a diagnostic tool covering the areas of organizational management, personnel management, finance and costs, marketing, planning and control of production and environmental management and health that meets the characteristics of the study's co-operatives and so would provide their development and subsequent applications by other institutions.